2022
DOI: 10.3389/feduc.2022.837714
|View full text |Cite
|
Sign up to set email alerts
|

The Role of L2 Motivational Self System and Grit in EFL Learners’ Willingness to Communicate: A Study of Public School vs. Private English Language Institute Learners

Abstract: Learning a second language (L2) is analogous to a journey replete with setbacks and discouragements. Given the pivotal role of communication in L2 learning, researchers have set out to identify factors that may influence L2 learners’ willingness to communicate (L2 WTC). To this end, the present comparative study attempts to investigate the role of the L2 motivational self-system and grit in learners’ L2 WTC in two different educational settings: public schools and private language institutes. L2 motivational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Successful verbal communication is an indispensable part of L2 education and human relations [ 1 , 4 , 12 , 46 ]. Although many educators may ascribe communication success to students’ communicative competence, research shows that willingness to use language authentically goes beyond linguistic issues [ 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful verbal communication is an indispensable part of L2 education and human relations [ 1 , 4 , 12 , 46 ]. Although many educators may ascribe communication success to students’ communicative competence, research shows that willingness to use language authentically goes beyond linguistic issues [ 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Ebn-Abbasi et al maintained that L2 WTC has a positive correlation with students’ motivational self-systems [ 1 ]. The impact of communication-related variables like L2 communication attitude, confidence, anxiety, and self-perceived competence on L2 WTC has also been examined [ 8 , 64 , 65 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Lee (2022) found only PE and enjoyment were predictors of all Korean cohorts’ L2 WTC (middle school: N = 137; high school: N = 323; and university students: N = 187). By comparing the strength of L2 grit (PE and CI) and learning motivation on L2 WTC among Iranian EFL learners across high school and private institutes, Ebn-Abbasi et al (2022) demonstrated only PE and classroom engagement, except for CI, exerted a significant effect on L2 WTC in both educational settings ( N = 308). A recent article by Khajavy and Aghaee (2022) reported that when other predictors were included in the structural equation model, only PE indirectly predicted L2 enjoyment and personal best goals reflected by Iranian English learners ( N = 226), indicating a mix of other factors might interfere with the function of grit as originally conceived.…”
Section: Resultsmentioning
confidence: 97%
“…In other words, those people who exhibit PERMA are happier and therefore more successful people. In a similar vein, many studies (e.g., MacIntyre and Vincze, 2017;Dewaele and Alfawzan, 2018;Khajavy et al, 2018Khajavy et al, , 2021Ebn-Abbasi et al, 2022) found positive correlations between positive emotions, motivational constructs and willingness to communicate (WTC) which are considered as crucial factors in language learning.…”
Section: Review Of the Literature Positive Psychology And Permamentioning
confidence: 91%